Community Compensation in the Perspective of Maslahah: A Review of Regent Regulation No. 62 of 2013 on the Construction of the Jambi-Rengat Toll Road in Batanghari Regency - Hartono, Sigit; Ritonga, A. Husein; Ishaq, Ishaq (Journal of Social Work and Science Education, 2025)
This study examined and analyzed community compensation from the perspective of maslahah (public benefit) by reviewing Regent Regulation No. 62 of 2013 regarding the construction of the Jambi-Rengat toll road in Batanghari Regency, Jambi Province. The selection of this regulation serves as the basis for determining the fundamental value of community compensation for land acquisition, which constitutes the primary object of this dissertation. This study employs a qualitative research design, adopting a sociological approach that integrates positive legal and religious perspectives. The methodology is based on field observations and a literature review, providing a comprehensive analysis of the legal provisions in force and their impact on society. This approach is developed and applied to analyze justice and fairness in the implementation of laws within the community. The findings indicate that Regent Regulation No. 62 of 2013 is no longer suitable for determining the base price of community compensation for land acquisition, particularly in the construction of the Jambi-Rengat toll road in Batanghari Regency. The issue lies in the discrepancy between the regulated compensation values and the actual market prices, which have significantly evolved over time. Although the local government has introduced a revised regulation, Regent Regulation No. 52 of 2021, the delay in its issuance rendered it ineffective, as compensation agreements between the community and toll road developers had already been settled. As the policy-making authority, the government must ensure that its regulations align with principles of justice and public welfare, rather than merely focusing on administrative convenience and national economic benefits. Consideration should be given to protecting the rights and well-being of affected communities.